2016
DOI: 10.1111/jgh.13078
|View full text |Cite
|
Sign up to set email alerts
|

The White Diet is preferred, better tolerated, and non‐inferior to a clear‐fluid diet for bowel preparation: A randomized controlled trial

Abstract: The White Diet was preferred and better tolerated by patients without detriment to the success of bowel preparation or colonoscopy performance, especially with the split-dose regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…There was also significantly less bloating, weakness, hunger, and interruption to daily activities with the White Diet. Although the duration of the dietary restriction was longer in the White Diet group, our group has previously reported that the daily median energy intake with the White Diet was twice that of a clear fluid diet15 which may contribute to the improved tolerance compared with a 24‐h clear fluid diet. Furthermore, the use of white color as a guide to choose food is a simple strategy which patients found significantly easier to follow and the flexibility of the White Diet allows patients to individualize the diet according to personal dietary preferences.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…There was also significantly less bloating, weakness, hunger, and interruption to daily activities with the White Diet. Although the duration of the dietary restriction was longer in the White Diet group, our group has previously reported that the daily median energy intake with the White Diet was twice that of a clear fluid diet15 which may contribute to the improved tolerance compared with a 24‐h clear fluid diet. Furthermore, the use of white color as a guide to choose food is a simple strategy which patients found significantly easier to follow and the flexibility of the White Diet allows patients to individualize the diet according to personal dietary preferences.…”
Section: Discussionmentioning
confidence: 86%
“…The White Diet, recently described by Butt et al .,15 is a pre‐colonoscopy low‐residue diet of white or cream‐colored foods. In that randomized controlled trial of 226 patients, the White Diet in conjunction with a 2‐L PEG with ascorbate bowel preparation was preferred by patients with less hunger and interference to daily activities without detriment to bowel preparation quality or colonoscopy performance compared with a clear fluid diet 15.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…) according to a computer‐generated randomization schedule. Patients in both arms received instructions for a low‐residue White Diet for 2 days prior to the procedure and split dose of the standard BP (PrepKit‐C). Standard BP is a combination of one sachet of PEG (Glycoprep‐C, consisting of macrogol 3350, sodium sulfate, sodium chloride, and potassium chloride, Fresenius Kabi Pty Ltd., Pymble, New South Wales, Australia) and two sachets of SP/MC (PicoPrep, consisting of sodium picosulfate 10 mg, magnesium oxide 3.5 g, citric acid 12.0 g, and aspartame 36 mg, Fresenius Kabi Pty Ltd.).…”
Section: Methodsmentioning
confidence: 99%